Expansion strategies of U.S. multinational firms - Hanson, Gordon H.; Mataloni, Raymond J, Jr; Slaughter, Matthew J. (NBER working paper series, 2001)
Recent theoretical work tends to characterize multinational enterprises as arising through either horizontal or vertical foreign direct investment (FDI). Empirical research tends to find stronger support for the former than for the latter. In this paper, we use recent, detailed data on U.S. multinational firms to revisit the question of why multinationals go abroad. We examine three types of foreign activities of U.S. multinationals: global outsourcing, the use of export platforms, and wholesale trading. Our results suggest that vertical FDI is more common than previous research suggests, and more generally that the foreign affiliates of multinationals span a diverse set of activities that each respond to policies and characteristics of host countries in quite different ways.